Automated Cerebrospinal Fluid Cell Counts Using the New Body Fluid Mode of Sysmex UF‐1000i. Issue 5 (24th August 2015) - Buoro, Sabrina; Apassiti Esposito, Sara; Alessio, MariaGrazia; Crippa, Alberto; Ottomano, Cosimo; Lippi, Giuseppe
Abstract: Background: We evaluated the new body fluid module on Sysmex UF1000‐i (UF1000i‐BF) for analysis of white blood cell (WBC) and red blood cell (RBC) in cerebrospinal fluid (CSF). Methods: WBC and RBC counting were compared between UF1000i‐BF and Fuchs–Rosenthal counting chamber in 67 CSF samples. This study also included the evaluation of between‐day precision, limit of blank (LoB), limit of detection (LoD), functional sensitivity (limit of quantitation, LoQ), carryover and linearity. Diagnostic agreement for differentiation between normal and increased WBC counts (≥5.0 × 10 6 /L) was also assessed. Results: The agreement between UF1000i‐BF and manual WBC counts was otpiaml in all CSF samples ( r = 0.99; y = 1.05 x + 0.09). A modest overestimation was noticed in samples with WBC < 30 × 10 6 /L ( r = 0.95; y = 1.21 x − 0.15). A good agreement was observed for RBC counts ( r = 0.98; y = 1.15 x + 0.55), particularly in samples with RBC ≥ 18 × 10 6 /L ( r = 0.98; y = 1.01 x + 8.90). Between‐day precision was good, with coefficient of variations (CVs) lower than 7.2% for both WBC and RBC. The LoBs were 0.1 × 10 6 WBC/L and 1.2 × 10 6 RBC/L, the LoDs were 0.7 × 10 6 WBC/L and 5.5 × 10 6 RBC/L, the LoQs were 2.4 × 10 6 WBC/L and 18.0 × 10 6 RBC/L, respectively. Linearity was excellent ( r = 1.00 for both WBC and RBC). Carryover was negligible. Excellent diagnostic agreement was obtained at 4.5 × 10 6 WBC/L cut‐off (sensitivity, 100%; specificity, 97.4%). Conclusion: The UF1000i‐BF provides rapid and accurate WBC and RBC counts in clinically relevant values of CSF cells. The use of UF1000i‐BF may hence allow to replace routine optical counting, except for samples displaying abnormal WBC counts or abnormal scattergram distribution, for which differential cell counts may still be required.